Ceramics and the human figure - Garcia, Edith (Ohio, USA A & C Publishers, 2012)
1 Revisiting history -- 2 The human condition and everyday life -- 3 Gender and social issues -- 4 Hybrids -- 5 Disappearance -- 6 Techniques.
Includes index.
Keywords: Ceramics; Human figure in art